2022
DOI: 10.3390/su14063398
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable Development in Education from Students’ Perspective—Implementation of Sustainable Development in Curricula

Abstract: Education for sustainable development is a method of teaching aimed at developing awareness, competence, knowledge, skills, and attitudes in the field of environmental protection in such a way that each activity related to its operation supports the satisfaction of the needs of future generations. In the face of environmental and social challenges, these are key competencies that require significant changes in university curricula, supporting a sustainable and innovative economy. This article aims to present t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 46 publications
0
16
0
Order By: Relevance
“…Another study showed that the assessment and prioritization of sustainable development goals differed according to the field of study. While engineering or production management students ranked economic growth as the most important, environmental engineering students prioritized the problems of health, hunger, and well-being [ 24 ]. Regarding willingness to adopt climate-friendly lifestyles, the findings of the present study are in line with the results of an exploratory study by Reismann et al (2021) among patients of general practitioners and gynecologists in Germany [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another study showed that the assessment and prioritization of sustainable development goals differed according to the field of study. While engineering or production management students ranked economic growth as the most important, environmental engineering students prioritized the problems of health, hunger, and well-being [ 24 ]. Regarding willingness to adopt climate-friendly lifestyles, the findings of the present study are in line with the results of an exploratory study by Reismann et al (2021) among patients of general practitioners and gynecologists in Germany [ 19 ].…”
Section: Discussionmentioning
confidence: 99%
“…Due to its higher expected significance in the future, viable solutions for interdisciplinary courses need to be implemented at all levels of higher education. Rethinking HEI structures and programmes through an interdisciplinary perspective by implementing courses and projects can be beneficial for achieving sustainability [82][83][84], and students exposed to interdisciplinarity have shown an increased proclivity for innovation, despite the difficulties associated with balancing between disciplines [85]. Such courses and programmes should provide the students with "communication skills", "high-order cognitive skills", and knowledge of disciplines and interdisciplinarity, all while balancing with discipline-specific content [86].…”
Section: Involving Students In Interdisciplinary Research and Industr...mentioning
confidence: 99%
“…The overarching intent of the SDGs in higher education institutions (HEIs) reflect an integration of structures to allow curriculum development to demonstrate an institutional commitment to addressing the needs of today through teaching and research which prepare students to address the challenges of future generations (Fauzi et al, 2022). HEIs are a critical stakeholder in developing transformational leaders through the way in which they “culminate and assimilate the knowledge of sustainability that would eventually be diffused within the community and society” (Fauzi et al, 2022, p. 3) and serve as “drivers of social transformation” (Zwolińska et al., 2022, p. 4). Thus, undergraduate leadership education is positioned to implement courses and programs that develop students with global competencies for addressing the complex social and global issues framed through the SDGs.…”
Section: Introductionmentioning
confidence: 99%
“…“Achieving the SDGs by 2030 will require leaders who can transcend physical boundaries, and social, cultural, and political barriers to influence large‐scale collaboration and cooperation” (Van Norren & Beehner, 2021, p. 36). Existing and incoming leadership courses and programs focused on intercultural competency, civic engagement, and core cognitive development through transformative learning are essential for continued progress toward achievement of the SDGs (Fauzi, 2022; Forbes, 2014; Gulacar, 2022; Z wolińska et al., 2022). Leadership educators have an opportunity to impart the interdisciplinary, transferable knowledge needed to equip students with competencies for addressing complex, global challenges identified within the SDGs by utilizing them for problem‐based learning.…”
Section: Introductionmentioning
confidence: 99%